Factors associated with health-related quality of life in patients with Crohn's disease in Iran: A prospective observational study - Karami, Hassan; Shirvani Shiri, Maryam; Ebadi Fard Azar, Farbod; Bagheri Lankarani, Kamran; Ghahramani, Sulmaz; Rezapour, Aziz; Tatari, Maryam; Heidari Javargi, Zahra (Frontiers in Medicine, 2023)
ABSTRACT The purpose of this study was to assess the health-related quality of life (HRQoL) of Crohn's disease (CD) patients in Iran. This was a one-year prospective observational study of moderate to severe CD. Patients' HRQoL were measured using the EQ-5D 3L, EQ-VAS, and IBDQ-9 tools. HRQoL among CD patients were compared using the T-test, Mann-Whitney, Chi-square, and Fisher's exact tests. To discover factors influencing patients' HRQoL, multivariate linear regression and multivariate logistic regression tests were utilized. The study included 222 CD patients, with a mean age of 34.67 and mean disease duration of 7.32 years. The dimensions with the worst reported “relatively or extreme problems” were P/D: 77.5 and A/D: 63.1 percent. Employment, having “other chronic diseases”, and ADA consumption were the most important independent predictors of HRQoL in CD patients, (β = 0.21 [EQ-5D index], β = 19.61 [EQ-VAS], β = 12.26 [IBDQ-9], OR: 0.09 [MO], OR: 0.12 [UA], OR: 0.21 [P/D], OR: 0.22 [A/D]), (β = -0.15 [EQ-5D index], β = -5.84 [IBDQ-9], β = -11.06 [EQ-VAS], OR: 4.20 [MO], OR: 6.50 [UA]), and (OR: 2.29 [A/D]) respectively. Unemployment, presence of other chronic conditions had the greatest negative impact on HRQoL of CD patients. There were significant differences in the probability of reporting ‘‘relatively or extreme problems’’ in the SC and A/D dimensions between patients using adalimumab (ADA) and infliximab (IFX). Keywords: Crohn's disease, Health-related quality of life, EQ-5D, IBDQ-9, EQ-VAS, Associated Factors.